2016
DOI: 10.1038/srep23737
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous reactive species induced by a surface air discharge: Heterogeneous mass transfer and liquid chemistry pathways

Abstract: Plasma-liquid interaction is a critical area of plasma science and a knowledge bottleneck for many promising applications. In this paper, the interaction between a surface air discharge and its downstream sample of deionized water is studied with a system-level computational model, which has previously reached good agreement with experimental results. Our computational results reveal that the plasma-induced aqueous species are mainly H+, nitrate, nitrite, H2O2 and O3. In addition, various short-lived aqueous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
187
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(192 citation statements)
references
References 25 publications
5
187
0
Order By: Relevance
“…Water is a polar liquid and its conductivity changes when exposed to high voltage (Šunka, ), thus making the application of NTP to a wet surface or a liquid substrate a more complicated process (Bruggeman et al., ; Liu et al., ). It has been reported that the inactivation of microorganisms by plasma in a liquid substrate is mediated by the liquid phase and it is important to understand the complete NTP–liquid interactions to optimize food and medical applications (Bruggeman et al., ; Liu et al., ). Presence of humidity in the carrier gas also leads to modifications in the reactive species of the NTP system and acts as a barrier for the NTP reactive species to penetrate within the liquid substrate (Gorbanev, O'Connell, & Chechik, ; Krohmann et al., ).…”
Section: Ntp–liquid Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is a polar liquid and its conductivity changes when exposed to high voltage (Šunka, ), thus making the application of NTP to a wet surface or a liquid substrate a more complicated process (Bruggeman et al., ; Liu et al., ). It has been reported that the inactivation of microorganisms by plasma in a liquid substrate is mediated by the liquid phase and it is important to understand the complete NTP–liquid interactions to optimize food and medical applications (Bruggeman et al., ; Liu et al., ). Presence of humidity in the carrier gas also leads to modifications in the reactive species of the NTP system and acts as a barrier for the NTP reactive species to penetrate within the liquid substrate (Gorbanev, O'Connell, & Chechik, ; Krohmann et al., ).…”
Section: Ntp–liquid Interactionsmentioning
confidence: 99%
“…After exposing to the gas plasma, the reactive species in the liquid initiate many postdischarge reactions within the liquid. The liquid chemical reaction pathways and the diffusion coefficients of NTP reactive species in the liquid phase are presented in Figure (Liu et al., ; Verlackt, Van Boxem, & Bogaerts, ) and Table , respectively. In Figure , the blue lines indicate the diffusion process, whereas the black lines represent the chemical reactions.…”
Section: Ntp–liquid Interactionsmentioning
confidence: 99%
“…One advantage of direct treatment is that the short-lived species such as O, OH, NO, and even the electric field or UV produced by the plasma [11,12] could be possibly effective; some reports indicate this type of plasma treatment could enhance or modify the germination and/or growth of the oilseed rape seeds [13], bean and wheat seeds [14][15][16]. Direct plasma treatments on tomato, radish and mulungu gave also positive effects [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the studies have focused on the activity of species generated in the gas phase, however, the lifetime of chemical species generated in the gas phase is relatively short, as they are quenched rapidly during their frequent collisions with molecules or other species. High reactivity and short lifetime also means that only a fraction of the species generated during plasma treatment are able to penetrate the gas−liquid interface to reach the intended target4, potentially limiting the efficiency of gas phase plasma inactivation against microorganisms in a moist environment or in bulk liquids.…”
mentioning
confidence: 99%